Ukrainian and English Motivational Self System of Minority Learners in Transcarpathia - Henkel, Beatrix (Working Papers in Language Pedagogy, 2010)
The investigation reported in the present article discusses the differences between the motivational disposition of ethnic minority learners to studying a state language as compared to their motivation to studying a foreign language. Dörnyei’s (2005) L2* Motivational Self System Theory serves as the dominant theoretical framework of the current research. Altogether 147 questionnaires were collected from Hungarian minority secondary school learners in Ukraine studying in the tenth and eleventh forms. The results confirm the presence of each of the three key dimensions in Dörnyei’s theory, namely, the Ideal L2 Self, the Ought-to L2 Self, and Learning Experience in the English motivational self system of the learners. However, only one of the named key dimensions was incorporated in the learners’ Ukrainian motivational self system and it was supplemented by attitudes learners have towards learning the language of the linguistic majority of Ukraine, i.e., Ukrainian. The findings of the study confirm that the dimensions of the L2 Motivational Self System adequately explain the language learning motivation construct of minority learners of English; however, to examine its feasibility to describe the Ukrainian language motivation of learners further research is needed.